Spirituality, creativity and positivism on the life path as a prerequisite for the successful formation of gifted person [Духовность, креативность и позитивизм на жизненном пути как предпосылки успешного становления одаренной личности] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (Житомир : Вид-во ЖДУ ім. І. Франка, 2010)
В статье обосновывается, что духовность выступает ключевой предпосылкой формирования студенческой одаренности, успешное проявление которой стабилизируется и находит свое дальнейшее развитие при позитивном социоокружении. In this paper the spirituality as a key presupposition of student’s natural gifts formation is grounded. It is shown that the student’s natural gifts can be successfully stabilized and receive further development within a positive socio-environment.
Keywords: духовность; позитивизм; одаренность; студенчество; spirituality; positivity; natural gifts; student period